Conversations with place: an autoethnographic exploration of art jewellery as translative practice in the Groot Drakenstein, South Africa - Groenewald, Joani (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosh University, 2025.